2021
DOI: 10.1161/atvbaha.120.315421
|View full text |Cite
|
Sign up to set email alerts
|

Role of LOX-1 (Lectin-Like Oxidized Low-Density Lipoprotein Receptor 1) as a Cardiovascular Risk Predictor

Abstract: Atherosclerosis, the underlying cause of cardiovascular disease (CVD), is a worldwide cause of morbidity and mortality. Reducing ApoB-containing lipoproteins—chiefly, LDL (low-density lipoprotein)—has been the main strategy for reducing CVD risk. Although supported by large randomized clinical trials, the persistence of residual cardiovascular risk after effective LDL reduction has sparked an intense search for other novel CVD biomarkers and therapeutic targets. Recently, Lox-1 (lectin-type oxidized LDL recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 117 publications
0
66
0
1
Order By: Relevance
“…The identification of an ipsilateral non-stenotic carotid plaque with or without high-risk features is not sufficient to reclassify ESUS as stroke due to large vessel disease. Further research is, therefore, needed to determine whether combination of vascular imaging findings, clinical data, and candidate biomarkers of plaque progression/instability or atheroembolism ( 46 – 82 ) into multiparameter scores could improve the ability to (1) establish a causal link between ESUS and a non-stenotic carotid plaque, (2) predict plaque progression or stroke recurrence, and (3) select patients who might benefit from adjuvant anti-inflammatory and lipid-lowering therapies as briefly discussed in the next section. Some biomarkers of plaque progression and instability that warrant further investigation specifically in patients with ESUS are presented in Table 3 .…”
Section: Challenges Of Establishing Causal Link With Strokementioning
confidence: 99%
“…The identification of an ipsilateral non-stenotic carotid plaque with or without high-risk features is not sufficient to reclassify ESUS as stroke due to large vessel disease. Further research is, therefore, needed to determine whether combination of vascular imaging findings, clinical data, and candidate biomarkers of plaque progression/instability or atheroembolism ( 46 – 82 ) into multiparameter scores could improve the ability to (1) establish a causal link between ESUS and a non-stenotic carotid plaque, (2) predict plaque progression or stroke recurrence, and (3) select patients who might benefit from adjuvant anti-inflammatory and lipid-lowering therapies as briefly discussed in the next section. Some biomarkers of plaque progression and instability that warrant further investigation specifically in patients with ESUS are presented in Table 3 .…”
Section: Challenges Of Establishing Causal Link With Strokementioning
confidence: 99%
“…The analysis revealed also that SR-BI correlates with one more parameter -Lectin-type oxidized LDL receptor 1 (LOX-1). In the latest publications (2020 and 2021), LOX-1 is presented as a promising target for early diagnosis and cardiovascular risk prediction [39][40][41]. Such enthusiastic announcements made us expect to nd higher levels of LOX-1 in people with stroke, after a myocardial infarction or with obesity, but no such association was found in our geriatric population.…”
Section: Discussionmentioning
confidence: 93%
“… 21 , 23 , 24 In the field of cardiovascular, it is well-known that sLOX-1 levels can reveal the severity of acute coronary syndrome and is related to the prognosis of coronary artery disease. 20 , 24 In the research of cerebrovascular disease, sLOX-1 levels were elevated in patients with ischemic stroke and transient ischemic attack, 26 28 and the elevated were more significantly in severe patients compared to the mild stroke group. 28 Which was confirmed in our study further, we found the proportion of severe neurological deficit at admission in patients with the low level of sLOX-1 was10.14%, much lower than the other 2 groups (21.74% for moderate level of sLOX-1 group and 28.99% for the high level of sLOX-1group).…”
Section: Discussionmentioning
confidence: 98%